ADEQUACY OF SUPPLEMENTARY FEEDING IN THE FIRST YEAR OF LIFE - Lucena, Regiane Fixina de; Carvalho, Danielle Franklin de; Medeiros, Carla Campos Muniz; Farias, Camilla Ribeiro Lima de; Costa, Ivelise Fhrideraid Alves Furtado da; Vianna, Rodrigo Pinheiro de Toledo; Cardoso, Maria Aparecida Alves (REVISTA CEREUS, 2015)
To evaluate the adequacy of complementary feeding in the sixth and twelfth month of life in children attended at the primary health care of Campina Grande-PB- Brazil, and to describe the associated sociodemographic and maternal factors. Overall, 202 children in the first year of lifewere followed between October 2005 and June 2008. During interviews in family health units, monthly questionnaires about food introduction, sociodemographic and maternal factors were applied. Food adequacy was analyzed based on recommendations from the Ministry of Health for the first and second semesters of life. Chi-square and student T tests were used to examine associations between nutritional adequacy and child, maternal andsociodemographic variables. Only one child received adequate food introduction in the first year of life. The population had low income and education. Statistical association was found between maternal age and the introduction of carbohydrates as well as maternal work and the introduction of food preparations. The introduction of sugar was associated with marital cohabitation, per capita income and number of pregnancies (p<0.05). The introduction of food was inadequate, showing associations between certain kind of food and maternal and sociodemographic factors, suggesting the need for more effective nutrition education in the primary health care. KEYWORDS: supplementary feeding; breastfeeding; infant nutrition.